THE USE OF GABIONS IN THE LANDSCAPE DESIGN OF HIGHWAYS AND CITY STREETS (American Journal of Technology and Applied Sciences, 2023)
One of the most important problems of modern road engineering is to improve people's environment and create healthy and comfortable living conditions in cities with high demands on architecture in general and landscape architecture in particular. In solving this problem, green construction, which covers many issues of architectural, planning, engineering and biological nature, plays an important role. In our country, gabions are widely used for artistic decoration of highways, road stabilization and erosion control of slopes, structural purposes in highway architecture.